Simulation Study of Area Effect at Shock Initiation of Shield Explosive. Issue 1 (October 2020) - Jiang, Lei; Li, Ruibo; Qin, Zhen; Xue, Yan
Abstract: To get the rule of area effect changing with diameter, velocity and height of projectile and thickness and material of target, the process of projectile perpendicular impacting target was simulated by AUTODYN and the pressure and velocity of observing points that set at the opposite side of hitting were analysed. And then simulation value and calculation value of experience formula in existence were compared. The result shows that experience formula is feasible, which provides a new method for the study of shield explosive shock initiation.